Epard/Porsch House - Dan Rockhill (Oz, 1999)
The Compagnons du Devoir, a traditional French Guild, sets goals for its members of professional, moral, and spiritual perfection “through manual work and the simultaneous nurturing of the conscious.” Jean Bernard, a present day leader has written: We think that true communication, love perhaps, cannot arise except through an exchange, and that the mind and hand, united at the source of movement and its search for completion and reunited at the moment of highest achievement in the great vocations, are complementary in the deep workings of the whole.